Gastrointestinal parasites in captive and free-ranging Cebus albifrons in the Western Amazon, Ecuador. Issue 3 (December 2017) - Martin-Solano, Sarah; Carrillo-Bilbao, Gabriel A.; Ramirez, William; Celi-Erazo, Maritza; Huynen, Marie-Claude; Levecke, Bruno; Benitez-Ortiz, Washington; Losson, Bertrand
Abstract: Currently, there is a lack of surveys that report the occurrence of gastrointestinal parasites in the white-headed capuchin monkey ( Cebus albifrons ). We therefore assessed the presence and richness (= number of different parasite genera) of parasites in C. albifrons in wildlife refuges (n = 11) and in a free-ranging group near a human village (n = 15) in the Ecuadorian Amazon. In the 78 samples collected (median of 3 samples per animal), we identified a total of 6 genera of gastrointestinal parasites, representing protozoa, nematodes, acanthocephalans and cestodes. We observed a high prevalence (84%) across the 26 individuals, with the most prevalent parasite being Strongyloides sp. (76.9%), followed by Hymenolepis sp. (38.5%) and Prosthenorchis elegans (11.5%). We found Entamoeba histolytica/dispar/moskovskii/nuttalli and Capillaria sp. in only a minority of the animals (3.8%). In addition, we observed unidentified strongyles in approximately one-third of the animals (34.6%). We found a total of 6 parasite genera for the adult age group, which showed higher parasite richness than the subadult age group (5) and the juvenile age group (3). Faecal egg/cyst counts were not significantly different between captive and free-ranging individuals or between sexes or age groups. The free-ranging group had a higher prevalence than the captive group; however, this difference was not significant. The only genus common to captive and free-ranging individuals was Strongyloides sp. The high prevalence of gastrointestinal parasites and the presence of Strongyloides in both populations support results from previous studies in Cebus species. This high prevalence could be related to the high degree of humidity in the region. For the free-ranging group, additional studies are required to gain insights into the differences in parasite prevalence and intensity between age and sex groups. Additionally, our study demonstrated that a serial sampling of each individual increases the test sensitivity. Graphical abstract: Image 1 Highlights: This study brings new information about primate parasites to Ecuador. We analyse the prevalence, richness and FECC among the two habitats, sex and age. Adults harbour more genera of parasites than subadults and juveniles. Sampling effort was essential to find a good number of parasites genera. E. histolytica/dispar and P. elegans were found only in captive individuals.